Penguatan Nasionalisme Generasi Z pada Era Disrupsi sebagai Upaya Peningkatan Nilai-Nilai Karakter Bangsa di SMA Negeri 1 Kelapa Kabupaten Bangka Barat: Strengthening Generation Z's Nationalism in the Era of Disruption as an Effort to Increase National Character Values at SMA Negeri 1 Kelapa West Bangka Regency - Suntara, Reza Adriantika; Satrio, Ndaru; Asista, Aruna (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The disruption era has presented a dynamic pattern of life in all aspects; this has also touched the realm of national and state life. Generation Z, or the younger generation as supporters of the nation's future, is one part of life experiencing turmoil and disruption. Digital activities close to the younger generation have resulted in many positive and negative things. This is a good catalyst for the nation's progress and a bigger challenge in national life. Instilling nationalism as part of the nation's character values for the younger generation is necessary and must be instilled massively and sustainably to keep the younger generation from leaving the values of a good life that have long been adhered to by the Indonesian nation. Based on this, the service team from Universitas Bangka Belitung considers that strengthening nationalism for Generation Z needs to be conveyed through socialization steps to increase understanding and internalization of national character values.